PENGARUH PENGAWASAN,KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. TRIPLUS HITECH - Juniyati, Rita; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2021)
This research purpose to test and analyze the influence supervision,discipline and motivation to employee performance at PT. Triplus Hitech. Data collection was done by distributing quests with as many samples 114 respondent and using a quantitative descriptive approach. Data analysis used was statistical analysis in the form of multiple linear regression test. t test result show that the value supervision is 12.412> 1.981 with sig 0.000 1.981 with sig 0.000 1.981 eith sig 0.031 2.687 with sig 0.000<0.05, so simultaneously the variables of supervision,discipline and motivation have a significant effect on employee performance.